On exact order estimates of N-widths of classes of functions analytic in a simply connected domain - Vakarchuk, S. B. (Ukrains’kyi Matematychnyi Zhurnal, 1996)
In the spaces E q(Ω), 1 < q < ∞, introduced by Smirnov, we obtain exact order estimates of projective and spectral n-widths of the classes W r E p(Ω) and W r E p(Ω)Ф in the case where p and q are not equal. We also indicate extremal subspaces and operators for the approximative values under consideration.